2017
DOI: 10.4244/eij-d-16-00677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of procedural and clinical outcomes with Evolut R versus Medtronic CoreValve: a Swiss TAVI registry analysis

Abstract: Thirty-day clinical outcomes were favourable and comparable between the Evolut R and the CoreValve bioprosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 26 publications
4
21
1
Order By: Relevance
“…To our knowledge, this is the first study that compares individually the new large size self‐expandable 34 mm valve with its 31 mm predecessor. To date, studies comparing all‐size Evolut‐R with older CoreValve, demonstrated comparable 30‐day clinical outcomes, while a small single‐center cohort has shown reduced rates of more‐than‐mild PVR and higher device success with the new‐generation Evolut‐R device …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that compares individually the new large size self‐expandable 34 mm valve with its 31 mm predecessor. To date, studies comparing all‐size Evolut‐R with older CoreValve, demonstrated comparable 30‐day clinical outcomes, while a small single‐center cohort has shown reduced rates of more‐than‐mild PVR and higher device success with the new‐generation Evolut‐R device …”
Section: Discussionmentioning
confidence: 99%
“…The latest generation devices have successfully mitigated paravalvular leak with the addition of sealing skirts, ability to recapture and reposition, and optimized sizing based on CT. In contrast, the rate of permanent pacemaker implantation has remained stubbornly high . Procedural strategies including high implantation site may help to prevent new heart block .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, despite many European national registries (15,(17)(18)(19)(20)(21) and randomized trials-for which direct translation of their results into a daily clinical practice may be limited by strict inclusion and exclusion criteriathe study by Brennan et al provides unique data on TAVR outcomes derived from a large real-world cohort of patients and confirms the results of the major randomized trials. The propensity-matching was used to reduce selection bias and limit interpretation errors due to confounding factors.…”
mentioning
confidence: 58%
“…In this rapidly evolving field the valves implanted in this cohort-Edwards SAPIEN and Medtronic CoreValve prostheses in 67% and 33%, respectively are no longer used now that the latest generation prostheses (respectively the Edwards S3 and Evolut R and Pro) have shown their advantages (13)(14)(15). Furthermore, the rate of transfemoral approach (76.3%) was rather low considering that nowadays with the access size reduction more than 90% of procedures are performed by transfemoral approach in most centers.…”
mentioning
confidence: 99%